And the winner is-- : using awards programs to promote your company and encourage your employees - Leverence, John (Merritt Pub., 1997)
In a time when traditional measures of industry and professional status have lost their impact, awards mean more than ever for people and businesses. Proof? Corporate America's interest in quality awards like the Malcomb Baldridge medal.